Proceedings of the Health Science International Conference (HSIC 2017) 2017
DOI: 10.2991/hsic-17.2017.29
|View full text |Cite
|
Sign up to set email alerts
|

Propolis Trigona sp. Mouthwash Efectiveness in Lowering Anaerobic Gram-Negative Bacteria Colonies

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Another study showed that periodontal therapy using 10% Brazilian propolis was effective in treating gingivitis and chronic periodontitis (Cairo et al, 2006). A study by Samad et al (2017) proves that mouthwash containing 5%, 7.5%, and 10% propolis was effective in reducing gram-negative anaerobic bacteria.…”
Section: Introductionmentioning
confidence: 99%
“…Another study showed that periodontal therapy using 10% Brazilian propolis was effective in treating gingivitis and chronic periodontitis (Cairo et al, 2006). A study by Samad et al (2017) proves that mouthwash containing 5%, 7.5%, and 10% propolis was effective in reducing gram-negative anaerobic bacteria.…”
Section: Introductionmentioning
confidence: 99%